DEPTH OF TUMOR INVASION AS INDICATOR OF MALIGNANT PROGRESSION IN PATIENTS WITH LOWER LIP SQUAMOUS CELL CARCINOMA WITH AND WITHOUT NECK LYMPH NODE METASTASIS - Kakasheva-Mazhenkovska, Lena; Mitevska, Elida; Kostadinova Petrova, Irena; Janevska, Vesna (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Squamous cell carcinoma (SCC) of the lower lip is a relatively rare carcinoma, but it is the most common carcinoma in the oral cavity and accounts for approximately 25%-30% of all oral malignant tumors. Prognosis of patients with lower lip SCC is predominantly dependent on stage of the disease, but recent research suggest that neoplasm morphological characteristics can have a significant influence on its progression and consequently on patientâ€™s outcome. The aim of this study was to determine the role of depth of neoplasm invasion in the process of tumor progression, that is, in the onset of neck metastases in patients with lower lip squamous cell carcinoma and to correlate it with the neoplasm grade. The study comprised 60 tumor tissue specimens obtained from patients with lower lip SCC. The examined group consisted of 45 specimens from patients without metastasis and 15 specimens from patients with metastasis in the regional lymph nodes. Histopathological sections were made with paraffin technique and stained with H.E. method. Depth of invasion was measured with the software for histomorphological morhometry. There was a difference in the depth of stromal invasion in lower lip SCC, which was registered in the neoplasms of different histological differentiation and it was statistically significant (p=0.00001) according to the Kruskal-Wallis test. The difference in the depth of stromal invasion in lower lip SCC registered in neoplasms of patients without metastases and in patients with metastases was statistically significant (p=0.000083). Depth of neoplasm invasion is a parameter that can be used as an indicator for neoplasm progression, that is, as an indicator for neck metastases in patients with squamous cell carcinoma of the lower lip.   Keywords : squamous cell carcinoma SCC, lower lip, depth of stromal invasion, neoplasm differentiation, metastasis